POLITICAL CRISIS IN KAZAKHSTAN IN 2022 AND THE ROLE OF RUSSIA IN THE SETTLEMENT OF THE CONFLICT - M. Sh. Dzhantaliyeva (Современная наука и инновации, 2023)
The January events of 2022 in Kazakhstan stirred up the world community, forcing it to talk again about a new wave of ―color revolutions‖, the instability of authoritarian political regimes and the need to ―deepen democratic processes‖. However, the threat that arose was stopped in a timely manner and the country returned to normal. These events showed an effective method for resolving such conflicts. Russia has a unique (priceless) experience in conducting this kind of military operations. An experience that forced the West to take a completely new look at its own policies. In this story, we are primarily interested in the peacekeeping mission and the ability of the authorities and society to engage in constructive dialogue, the search for rational ways of reconciliation and the ability to search for new meanings. The article provides an analysis of the events that revealed the problematic blocks of the modern Kazakhstani political system, the reasons for those tragic events for the recent political history of Kazakhstan are indicated.